Māori Medium Teachers: Getting the Professional Development they Need - Meri Marshall; Tabitha McKenzie (New Zealand Journal of Teachers' Work)
In 2007, the Ministry of Education commissioned an evaluation of three Māori medium junior reading series: He Purapura, Ngā Kete Kōrero and He Kohikohinga. Questionnaires were completed by 84 teachers in Level 1, 81-100% immersion Māori settings, and semi-structured focus group interviews were undertaken with 15 teachers and 14 literacy experts. Two case studies and a review of texts were also undertaken. This article explores an emerging theme from the evaluation data around professional development (PD). Teachers and literacy experts identified several key features important for effective PD, including the quality of pre- and in-service education, second language acquisition training and PD that is tailored to meet the teachers’ needs. The findings indicate that teachers should have access to ongoing opportunities to develop their pedagogical and content knowledge and to have sufficient training in the use and implementation of reading resources and their support materials after they are distributed to schools.